Synthesis of pyrroles by nickel-catalysed arylative cyclisations of alkynamides - Chung, Chieh-Hsu (2019)
A nickel-based catalytic system for the anti-carbometallative cyclisations of alkynamides to arylboronic acids is described. The reactions proceed using catalytic nickel and (rac)-Ph-PHOX, to provide alkenylnickel species which can undergo reversible E/Z-isomerisation, followed by cyclisation onto an N-tosylamide to give 2,3,4-trisubstituted pyrroles.